Keanekaragaman Cacing Tanah (Kelas Oligochaeta) di Sekitar Tempat Pembuangan Akhir (TPA) Batu Layang Kecamatan Pontianak Utara - Ari Hepi Yanti, Arta Darmawan, Tri Rima Setyawati (Universitas Tanjungpura, 2014)
Batu Layang Landfills is pit land area which has low pH and high organic substance affects types of earthworm. This research aimed to know types of earthworm and factors that affected them in Batu Layang Landfills in North Pontianak. The Research was conducted from April to May 2013. Sampling used quadratic and hand-sorting method and was taken in three different location namely Musaceae plantation, Araceae plantation, and vacand land. Each location had five plots with 5x5 m of each and every plot contained 30x30m and was put randomly. Number of earthworms from quadran were collected, identified and counted. The research findings showed that types of earthworms found were Megascolex, Pheretima and Pontoscolex. Megascolex was the dominant type on every research site with 5.67 17.82 ind/m2 and achieved 0.8013, the highest dominant index on Station I/ Site I. The diversity index on the three sites was low ranging from 0.3979 to 0.6749 and evenness index was low ranging from 0.3622 to 0.6413.